Preparation of Chitosan Nanoparticles and Chitosan Nanoparticles Loaded with Azithromycin and the Study of Their Characterizations - Sarhan Rashid Sarhan (The Indian Veterinary Journal, 2025)
A noteworthy advancement in recent years has been the identification of nanoparticles, which are made of organic (carbon-based) or inorganic (metal-based) materials and range in size from 1 to 100 nm. This study's objective was to create, standardize, and analyze chitosan nanoparticles as well as chitosan nanoparticles that contained azithromycin. In the experiment, chitosan nanoparticles (CSNPs) and chitosan nanoparticles loaded with azithromycin were biosynthesized and characterized. (AZM-CSNPs) which is performed by spectrophotometry, (FTIR), (XRD), (SEM), (TEM), UV- spectrophotometer analysis and (DLS) Analysis. The results revealed atypical EM micrograph of CSNPs obtained by the reduction of CSNO3 solution. Applying Scherrer's  equation, the average grain size of the AZM-CSNPs generated during the bio-reduction process was calculated to be 31.5 nm. At a chosen concentration, CSNPs were 200 nm in size and had a zeta potential of 50 mV, whereas AZM-CSNPs were 51.1 nm in size and had a zeta potential of 50 mV.